Pengaruh Pendidikan Kesehatan Metode Demonstrasi terhadap Tingkat Pengetahuan dan Motivasi Penggunaan Alat Pelindung Diri (APD) pada Petani Desa Wringin Telu Kecamatan Puger Kabupaten Jember (The Effect of Health Education of Demonstration Methods to the - Sufyan Stauri; Wantiyah Wantiyah; Hanny Rasni (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Knowledge and motivation are factors influencing the using of PPE for farmers to protect them from injured or disease due to chemical fertilizers, insects, worm, sunlight, sharp objects, grinding machines, etc. Health education by demonstration method is one of learning method purposed to improve knowledge and motivation of using PPE of farmers. The purpose of this research was to find out the effect of health education by demonstration method toward the levels of knowledge and motivation in using PPE of farmers in Wringin Telu village. This research was a quasy experiment with two groups pretest-posttest treatment design. The population was 875 farmers with 30 respondents as sample, conducted by purposive sampling, and divided into two groups: 15 respondents as treatment group and 15 respondents as control group. Data were analyzed used t- test dependent and t- test independent with 95% CI. The result showed that there were significant defferences of knowledge levels (k) and motivation (m) before and after health education by demonstration methode in treatment group (pVk: 0,000; pVm: 0,000;α: 0,05). Meanwhile, there were no defferences of knowledge levels (k) and motivation (m) in control group (pVk: 0,418; pVm: 0,467;α: 0,05). Moreover, there were significant defferences of knowledge level and motivation between treatment grup and control group after health education by demonstration methode (pVk: 0,000, pVm: 0,000;α: 0,05). Overall, health education by demonstration method can improve both knowledge levels and motivation of using PPE. It is recommended for nurses to do health education by demonstration method to improve knowledge level and motivation of using PPE for farmers when they are working on the field Keywords: Health Education demonstration method, knowledge, motivation, personal protective equipment.